2021
DOI: 10.3389/fendo.2021.681647
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Spexin: (II) Functional Role as a Satiety Factor inhibiting Food Intake by Regulatory Actions Within the Hypothalamus

Abstract: Spexin (SPX) is a pleiotropic peptide with highly conserved protein sequence from fish to mammals and its biological actions are mediated by GalR2/GalR3 receptors expressed in target tissues. Recently, SPX has been confirmed to be a novel satiety factor in fish species but whether the peptide has a similar function in mammals is still unclear. Using the mouse as a model, the functional role of SPX in feeding control and the mechanisms involved were investigated. After food intake, serum SPX in mice could be up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 61 publications
2
4
0
Order By: Relevance
“…Additionally, immunoactivity was evident in the glands; it was negligible in both muscle layers of the stomach and was considered negative. This finding aligns with previous studies in rodents, where increased SPX signals were notably prevalent in the glandular stomach, particularly evident on the surface of the gastric mucosa involving foveolar cells, as well as in the lower mucosal layer characterized by parietal and chief cells constituting the gastric glands; discernible alterations in SPX immunostaining were absent in the muscle layers of both the forestomach and glandular stomach [30]. However, an intriguing divergence was observed within the cows' MP neurons, where no discernible immunoreactivity was detected.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, immunoactivity was evident in the glands; it was negligible in both muscle layers of the stomach and was considered negative. This finding aligns with previous studies in rodents, where increased SPX signals were notably prevalent in the glandular stomach, particularly evident on the surface of the gastric mucosa involving foveolar cells, as well as in the lower mucosal layer characterized by parietal and chief cells constituting the gastric glands; discernible alterations in SPX immunostaining were absent in the muscle layers of both the forestomach and glandular stomach [30]. However, an intriguing divergence was observed within the cows' MP neurons, where no discernible immunoreactivity was detected.…”
Section: Discussionsupporting
confidence: 92%
“…Mohammadi et al were the only researchers to examine the effects of exercise training on spexin [ 52 ]. Spexin is known to be an anorexigenic peptide in rodents and is thought to reduce energy intake in humans [ 55 , 56 ]. The chronic increase in fasting spexin concentration found from pre- to post-interventions in both groups was not associated with a change in appetite ratings.…”
Section: Resultsmentioning
confidence: 99%
“…SPX has been highly implicated in appetite regulation and food consumption [ 17 , 28 ]. In 2014, Jose et al found that chronic subcutaneous injection with SPX reduced 32% of total caloric intake in diet-induced obesity rats [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Spexin (SPX), a novel peptide hormone composed of 14 amino acids, was initially identified using a computational method based on Markov’s model screening of biologically active peptides [ 15 ]. This peptide is widely distributed in endocrine and epithelial tissues, including the liver [ 16 ], hypothalamus [ 17 ], adipose tissue [ 16 ], thyroid and anterior pituitary [ 18 ] of various species. The potential use of SPX as an anti-obesity treatment has been reported in recent studies.…”
Section: Introductionmentioning
confidence: 99%